Inventarisasi Dan Potensi Gulma Pada Tanaman Jagung (Zea Mays. L) Di Upt Patph Lebo Sidoarjo (Inventory And Potential Weeds In Corn Plants (Zea Mays. L) At Upt Patph Lebo Sidoarjo) - Faizah, Hanik; Nurvania Putri, Andini; Bahri, Saiful; Abdillah Ramadhan, Rachmat (Universitas Cokroaminoto Palopo, 2024)
Weeds are one of the Plant Pest Organisms (OPT) which have both advantages and disadvantages. Weeds can grow around plants very quickly, including in areas where corn is planted. This research aims 1. To describe the weed diversity index found in corn plants (Zea mays L.) at UPT PATPH Lebo Sidoarjo. 2. To determine the morphological structure of weeds found in corn plants (Zea mays L.) at UPT PATPH Lebo Sidoarjo. 3. To analyze various potential weeds found in corn plants (Zea mays L.) at UPT PATPH Lebo Sidoarjo. The method used is a survey using random sampling techniques with a plot system. The results showed that at stations I and II the most dominant plant was Portulaca oleracea (Purslane). The diversity index in the corn fields of UPT PATPH Lebo at stations I and II is 1.96, which means moderate diversity. which means H' is classified as medium (1<H'<H’3). The identified potential of weeds is as food, animal feed, medicine and ornamental plants.